A classroom experiment on the causes and forms of bounded rationality in individual choice - Anna Rita Bennato; Adrian Gourlay; Christopher Wilson (2020)
Bounded rationality is a key concept with implications across all areas of economics. To help students better understand the nature, causes and forms of bounded rationality in individual choice, we present a flexible classroom experiment. Beyond providing students with some first-hand evidence of bounded rationality, the experiment shows how a range of factors can prompt bounded rationality and illustrates how it can manifest itself in the form of different behaviours. The experiment can be conducted with any number of students and takes approximately 30 minutes to conduct, with a further 10-20 minutes to reflect and debrief.